Numerical simulation study on fracture propagation of zipper and synchronous fracturing in hydrogen energy development. (26th February 2019) - Guo, Tiankui; Wang, Xiaozhi; Li, Zhong; Gong, Facheng; Lin, Qiang; Qu, Zhanqing; Lv, Wei; Tian, Qizhong; Xie, Zhishuang
Abstract: Until now, hydraulic fracturing has played prominent role in increasing production of hydrogen energy such as natural gas, geothermal energy, natural gas hydrate. Hydrogen energy stimulation is realized by many methods. Such as multiple-clusters in staged fracturing, and fracture propagation guided by combined radial boreholes in different azimuths. In order to extend lateral stimulation area, the zipper fracturing is investigated continuously. However, the report on the zipper fracturing is limited to the post-frac productivity. In this study, model of simultaneous and zipper fracturing was established in ABAQUS to investigate the effect of six factors on the fracture propagation. The results showed that in simultaneous fracturing, the fracture network is formed spontaneously. With same brittleness of reservoir, fracture in zipper fracturing always propagates slightly longer than that in simultaneous fracturing. The results provide theoretically support for both fracturing modes, which helps design of well completion and fracturing operation parameters. Highlights: The effects of multiple factors on fracture propagation of the new crafts on hydraulic fracturing was studied. Simulation experiments of zipper fracturing were in-depth carried out. Simulation of fracturing cracking stress was studied. Difference of fracture propagation between simultaneous fracturing and zipper fracturing was discussed.